Spring-breeding and reproductive mode in Leptolalax khasiorum (Anura, Megophryidae) in north-eastern India - Tron, Ronald K. L.; Das, I.; Hooroo, Rupa N. K.; Rangad, D. (Folium Publishing Company, 2015)
We examined the breeding habitat, oviposition site and timing of breeding in Leptolalax khasiorum at its type locality at Mawphlang, Meghalaya State, north-eastern India. Surveys were conducted along a stream within a fragmented patch of forest for adults, tadpoles, eggs and nesting sites, with data collected monthly between January 2009 and December 2011. The species starts emerging from wintering microhabitats with the onset of the premonsoonal showers in February. Breeding activity (specifically, deposited eggs) was observed for a few weeks after emergence and lasted a few weeks between early March and April. Adults were found under rocks along the stream banks. Eggs are deposited on the underside of rocks that are flatly embedded on the gravel and over leafy bottom of the dry stream bed. The eggs of Leptolalax khasiorum are cream-colored, lacking an animal pole, and covered with a transparent jelly, showing adaptations for terrestrial development in sheltered microhabitats via avoidance of moisture loss and damage of eggs from solar radiation. In producing eggs out of water, showing free-swimming tadpoles, the reproductive mode can be classified as Mode 18, a first for a member of the genus Leptolalax. It is arguably the first report of terrestrial reproduction and parental care for a member of the family Megophryidae. Placement of eggs outside of water may coincide with low water levels of early spring, advantages of choice of timing being reduced competition for egg-laying sites and food for the larval and postlarval stages.